Manajemen Keuangan Pendidikan Anak Usia Dini Perspektif Wealth Management: Studi di TK Ceria Demangan Baru Yogyakarta - Raudhah Farah Dilla (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
Financial management constitutes a crucial element in the performance of the entire programs and activities within an institution. This research was conducted to study financial management practices in Early Childhood Education institution namely TK Ceria Demanagn Baru Yogyakarta through the perspective of wealth management. This research is a descriptive qualitative in which data were collected through interviews and documentations. The results showed that, 1) TK Ceria Demangan Baru managed its financial resources by setting aside students’ contributions for savings funds. This will be used for purposes outside of planned financial arrangement, 2) analysed through the perspective of wealth management, the institution’s financial Management is situated in